The association between problematic smartphone use and subjective well-being in Bangladeshi youths: Mediating role of sleep quality - Md. Rohmotul Islam; Oli Ahmed; Lutfun Naher; Md. Nurul Islam (Addictive Behaviors Reports)
Despite the remarkable contribution of smartphones in improving our lives, concerns have been raised about their uncontrolled usage, emphasizing its consequences on individual sleep and well-being. Therefore, we investigated the relationship between problematic smartphone use (PSU) and both positive and negative dimensions of subjective well-being (SWB) − subjective happiness and depressive symptoms, as well as the mediating role of sleep quality. A sample of 384 Bangladeshi youths (mean age = 18.99; 49.3 % female) were recruited through a convenience sampling technique and interviewed using a structured questionnaire that assessed PSU, sleep quality, subjective happiness, and depressive symptoms. The mediation analysis results indicated that sleep quality mediated the association between PSU and subjective happiness and depressive symptoms. The results also showed that subjective sleep quality, sleep disturbances, and daytime dysfunction were particularly responsible for the mediation effect. Thus, the findings highlight the necessity of designing sleep quality-enhancing interventions for youth to subside PSU’s detrimental effects on subjective well-being.